A Narrative Review of Control Strategies for Blood Glucose Regulation - Ndakara Abubakar, Isah; Essabbar, Moad; Saikouk, Hajar; Ahmed, El Hilali Alaoui (International Journal of Online and Biomedical Engineering (iJOE), 2024)
Effective blood glucose regulation is critical for managing type 1 diabetes mellitus (T1DM). This narrative review explores various control strategies for blood glucose regulation, incorporating simulations of the Bergman minimal model. We provide an in-depth review of both single and dual hormone systems, evaluating their respective advantages and limitations. The review focuses on the most widely adopted controllers, including proportional-integral-derivative (PID), model predictive control (MPC), and fuzzy logic controllers, highlighting their design principles and performances. Additionally, we discuss coordinated control strategies that integrate multiple controllers to enhance overall glucose regulation. Through this comprehensive analysis, we aim to identify the most effective control strategies for artificial pancreas systems, contributing to improved diabetes management.